1978
DOI: 10.1104/pp.62.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Gibberellin and Abscisic Acid Content as Related to Senescence of Detached Lettuce Leaves

Abstract: Levels of (GAs) and of absciic acid (ABA) Leaf senescence is associated with a decrease in endogenous cytokinin (16,22,23) and GAs3 (6,10) and an increase in ABA (6, 7). The involvement of cytokinins and GAs in leaf senescence has been indicated in studies that show the ability of these hormones to retard senescence. While it has been shown that ABA accelerates senescence in leaves, it is doubtful whether this hormone serves as a primary "senescence factor" (17,18). This doubt is strengthened by the frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 21 publications
3
27
0
1
Order By: Relevance
“…Senescence is affected by endogenous factors such as aging and hormones but also by environmental factors such as stress and nutrient supply (Gan and Amasino, 1997;Jing et al, 2002;Schippers et al, 2008). Specifically, the hormones ethylene and abscisic acid (ABA) have long been recognized as endogenous positive regulators of senescence (Hung and Kao, 2004;Lim et al, 2007), whereas gibberellin (GA) delays senescence in several species (Whyte and Luckwill, 1966;Goldthwaite and Laetsch, 1968;Chin and Beevers, 1970;Back and Richmond, 1971;Aharoni and Richmond, 1978;Kappers et al, 1998;Rosenvasser et al, 2006). Similarly, the supply of nutrients such as nitrogen, phosphorus, and metals is important during the senescence process (Lim et al, 2007;Wingler and Roitsch, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Senescence is affected by endogenous factors such as aging and hormones but also by environmental factors such as stress and nutrient supply (Gan and Amasino, 1997;Jing et al, 2002;Schippers et al, 2008). Specifically, the hormones ethylene and abscisic acid (ABA) have long been recognized as endogenous positive regulators of senescence (Hung and Kao, 2004;Lim et al, 2007), whereas gibberellin (GA) delays senescence in several species (Whyte and Luckwill, 1966;Goldthwaite and Laetsch, 1968;Chin and Beevers, 1970;Back and Richmond, 1971;Aharoni and Richmond, 1978;Kappers et al, 1998;Rosenvasser et al, 2006). Similarly, the supply of nutrients such as nitrogen, phosphorus, and metals is important during the senescence process (Lim et al, 2007;Wingler and Roitsch, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these plant responses are the direct result of physical changes accompanying loss of cell turgor (6) while other responses could be due to altered levels of plant growth regulators. Plants exposed to water-limited conditions have been shown to have elevated levels of ABA (25) and ethylene (2) and reduced amounts of cytokinin (16) and gibberellin (1).…”
mentioning
confidence: 99%
“…In soybean, Lindoo and Nooden (1 1) suggested that leaf senescence begins when leaves turn yellow. In other species, the onset of the senescence process had also been characterized by leaf yellowing (1,3,9). Sinclair and deWit (21) This investigation was conducted to study the leaf senescence processes in field-grown soybean.…”
mentioning
confidence: 99%